The development of computer package for the teaching and learning of space technology applications in surveying and natural resource management - A. Kadir, Abd. Majid; Desa, Ghazali; Omar, Abdullah Hisam (Universiti Teknologi Malaysia, 2002)
The advancement of Space and technology contributes to the rapid development of new methodologies in surveying and mapping such as Geodetic Astronomy and space-based positioning and mapping and Remote Sensing. On the other hand, the rapid development in information technology has made teaching and learning processes become more efficient. In these rapidly evolving fields, traditional textbooks are often become out of date before reaching the bookstores. Many of the course materials are continually changing. An electronic textbook offer many advantages and flexibities such as updating,application of a variety of presentation techniques and makes wide dissemination of the course materials possible. Hypermedia ( HTML) allows the interactive linking resource material under the control of user. Graphics, text, animation, cross-referencing and transition are examples of the variety of media that can be linked together in a multimedia platform. A virtual computer-based learning and teaching courseware package has been developed with a view to enhance the usage of the technology and promoting this knowledge through Information Technology. The courseware consists of two main modules : GPS and Astronomy. The courseware is available in CD-ROM and it is also made accessible to the public via internet ( geomatic.fksg.utm.my)